Polydopamine-coated i-motif DNA/Gold nanoplatforms for synergistic photothermal-chemotherapy - Bo Chen; Lan Mei; Rangrang Fan; Di Chuan; Yangmei Ren; Min Mu; Haifeng Chen; Bingwen Zou; Gang Guo (Elsevier, 2023)
The combination of photothermal therapy with chemotherapy has gradually developed into promising cancer therapy. Here, a synergistic photothermal-chemotherapy nanoplatform based on polydopamine (PDA)-coated gold nanoparticles (AuNPs) were facilely achieved via the in situ polymerization of dopamine (DA) on the surface of AuNPs. This nanoplatform exhibited augmented photothermal conversion efficiency and enhanced colloidal stability in comparison with uncoated PDA shell AuNPs. The i-motif DNA nanostructure was assembled on PDA-coated AuNPs, which could be transformed into a C-quadruplex structure under an acidic environment, showing a characteristic pH response. The PDA shell served as a linker between the AuNPs and the i-motif DNA nanostructure. To enhance the specific cellular uptake, the AS1411 aptamer was introduced to the DNA nanostructure employed as a targeting ligand. In addition, Dox-loaded NPs (DAu@PDA-AS141) showed the pH/photothermal-responsive release of Dox. The photothermal effect of DAu@PDA-AS141 elicited excellent photothermal performance and efficient cancer cell inhibition under 808 nm near-infrared (NIR) irradiation. Overall, these results demonstrate that the DAu@PDA-AS141 nanoplatform shows great potential in synergistic photothermal-chemotherapy.